Vineyard Fertilization Management for Iron Deficiency and Chlorosis Prevention on Carbonate Soil - Vladimir Zebec; Miroslav Lisjak; Jurica Jović; Toni Kujundžić; Domagoj Rastija; Zdenko Lončarić (Horticulturae, 2021)
Nitrogen fertilizer efficiency in grapevine production is an important objective for solving the trade-off between improving yield and quality in agroecosystems and reducing environmental impacts. Influence of soil nitrogen fertilization and Fe foliar application on iron dynamics in soil and grapevine leaves of the ‘Graševina’ cultivar on carbonate soil was conducted in a two-year study in 2018 and 2019. The experiment was settled in three replicates on a total of seven fertilization treatments that differed in used form of nitrogen fertilizer and foliar application of Fe before and after the flowering of the grapevine: control (C); calcium ammonium nitrate (KAN); calcium ammonium nitrate + foliar Fe (KAN+F); ammonium sulfate (AS); ammonium sulfate + foliar Fe (AS+F); ammonium sulfonitrate + foliar Fe (ASN+F); urea + foliar Fe (U+F). Mineral fertilization with acid-forming nitrogen fertilizers (AS and ASN) significantly affected local acidification of alkaline soil, i.e., reducing the actual and exchangeable soil pH reaction, which resulted in increased soil Fe availability. Despite the increase in soil iron availability, no increased iron bioaccumulation in the grapevine leaves was found in the flowering and veraison stages at treatments where foliar fertilization was omitted. Of all the observed treatments, only foliar fertilization had a positive effect on iron concentration in the grapevine leaves, which leads to the conclusion that this is an effective way to solve iron deficiency symptoms and chlorosis occurrence. The use of mineral fertilizers with acid-forming nitrogen fertilizers for many years can result in a reduction of required foliar treatments and thus significantly affect the ecological and economic aspects of grape production. Thus, integrated iron management is needed to meet the needs of the grapevine for this micronutrient and to reduce the occurrence of leaf chlorosis in carbonate soil.